Economic history of India under early British rule : from the rise of british power in 1757 to the accession of the queen Victoria in 1837 - "Dutt, Romesh" (London)
This is the Economic History of India, by ROMESH CHUNDER DUTT who undoubtedly was one of the great figures of his generation in India. Taken together, the two volumes cover the entire period of British rule in India,$1 (Bfrom the battle of Plassey in 1757 to the commencement of the 20th century. No history of the people of India, of their trades, industries, and agriculture, and of their economic condition under British administration, has been compiled till then. s
Keywords: Economics